Challenges in mammography education and training today: The perspectives of radiography teachers/mentors and students in five European countries. Issue 1 (February 2018) - Strøm, B.; Pires Jorge, J.A.; Richli Meystre, N.; Henner, A.; Kukkes, T.; Metsälä, E.; Sà dos Reis, C.
Abstract: Introduction: This study aims to explore current challenges in mammography education from the perspectives of radiography teachers, mentors and students. Methods: A qualitative study including two focus groups interviews, with radiography teachers/mentors (n = 5) and student radiographers (n = 5) exploring their perspectives on challenges in mammography education today. The content analysis methodology proposed by Graneheim and Lundman was applied to the interviews. Results: Three main categories were identified, each with subcategories identified as: (1) Building Bridges; Applying Theoretical knowledge in Practice, Performing Mammograms, Communication and Quality Assessment (2) State of the Art in Mammography; Personal Attitudes and Skills, Quality Awareness and Patient Care (3) Exploring the Curriculum; Time Constraints, Capacity in Clinical Placement, Multidisciplinary Field and Elective Course. Conclusion: The short study period allocated to this discipline and lack of material resources were considered the main limitations in mammography education, both impacting on the development of students' skills. Breast positioning, patient communication and quality control were considered key factors affecting mammography performance, patient experience and diagnostic outcome and should therefore be the core focus in mammography education. Highlights: Short study period and lack of material resources impacts the development of student's skills in mammography education. Breast positioning is a key factor affecting mammography performance. Focus on communication skills is pivotal for the patient's experience. Quality control awareness is crucial for diagnostic outcome in mammography.